1995
DOI: 10.1097/00005392-199508000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Prospective Study Comparing Radical Prostatectomy Alone Versus Radical Prostatectomy Preceded by Androgen Blockage in Clinical Stage B2 (T2bNxM0) Prostate Cancer

Abstract: Long-term followup data will be needed to determine whether there will be a lower incidence of biochemical relapse as determined by prostate specific antigen, local recurrence or metastasis, with an improvement in patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 18 publications
2
62
0
3
Order By: Relevance
“…Decrease in blood loss and operative diYculty after hormonal treatment were determined by Monfette et al (1989). Rassweiler et al (2001a, b) reported that 42 patients (23.3%) who underwent neoadjuvant therapy required a longer operating time and a higher transfusion rate than nonneoadjuvant patients, which indicated the increased technical diYculties, However, Soloway et al (1995) thought 3-month NHT makes the operation more diYcult for intense periprostatic reaction together with seminal vesicle adhesions, which had no impact on operative time or intraoperative bleeding. Similarly others did not Wnd any signiWcant diVerences in operative parameters (Macfarlane et al 1993;Goldenberg et al 1996;Schulman et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Decrease in blood loss and operative diYculty after hormonal treatment were determined by Monfette et al (1989). Rassweiler et al (2001a, b) reported that 42 patients (23.3%) who underwent neoadjuvant therapy required a longer operating time and a higher transfusion rate than nonneoadjuvant patients, which indicated the increased technical diYculties, However, Soloway et al (1995) thought 3-month NHT makes the operation more diYcult for intense periprostatic reaction together with seminal vesicle adhesions, which had no impact on operative time or intraoperative bleeding. Similarly others did not Wnd any signiWcant diVerences in operative parameters (Macfarlane et al 1993;Goldenberg et al 1996;Schulman et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although developments have encouraged the use of ADT for patients with advanced disease, reports in the early 1990s of potential benefit with neoadjuvant and adjuvant therapies have led to even more widespread use earlier in the natural history of the disease. [31][32][33] Such use of ADT may result in greater disease specific survival, as suggested by Messing et al 28 and Bolla et al…”
Section: Discussionmentioning
confidence: 99%
“…33 Indeed, from 1973 to 1990, mortality rates increased at a slow but constant rate in the Southeast Michigan region. Because the fall in prostate carcinoma mortality began in approximately 1993, we considered a number of sentinel events that occurred in the previous 10 -15-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Eine Senkung der Rate positiver Absetzungsränder kann somit als prognostisch wichtiges Kriterium für den Erfolg einer neoadjuvanten Hormontherapie gewertet werden. Wie in ⊡ Tabelle 1 dargestellt, findet sich eine signifikante Reduktion positiver Absetzungsränder in der Mehrzahl der publizierten Studien [1,14,11,22,39,34,45]. Die Ergebnisse von Bellavance u. Fradet [3] konnten sogar einen Vorteil einer maximalen Androgenblockade gegenüber einer einfachen Hormonblockade im neoadjuvanten Setting zeigen.…”
Section: Reduktion Positiver Absetzungsränderunclassified
“…Hier liegt eine häufige Fehleinschät-zung, zumeist eine Unterschätzung vor [4]. Die Tatsache, dass der Anteil organbegrenzter Tumoren aber deutlich höher ist als präoperativ eingeschätzt, unterstützt die These, dass es sich um ein Downstaging durch die Hormontherapie handelt [11,14,22,34,39,44,45]. Es findet sich nur ein Artikel von Dalkin et al [7], der keinen Downstagingeffekt in seinem Patientengut finden konnte.…”
Section: Downstagingunclassified